2009
DOI: 10.1681/asn.2008111166
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Prophylaxis Is Cost Effective in Transplant Patients at High Risk for Cytomegalovirus Infection

Abstract: The risk of late-onset cytomegalovirus (CMV) infection remains a concern in seronegative kidney and/or pancreas transplant recipients of seropositive organs despite the use of antiviral prophylaxis. The optimal duration of prophylaxis is unknown. We studied the cost effectiveness of 6-versus 3-mo prophylaxis with valganciclovir. A total of 222 seronegative recipients of seropositive kidney and/or pancreas transplants received valganciclovir prophylaxis for either 3 or 6 mo during two consecutive time periods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 33 publications
3
57
1
Order By: Relevance
“…In order to circumvent the occurrence of late HCMV disease after prophylaxis, attempts have been made to prolong prophylaxis to 6 months [25,26]. In our study, late onset HCMV disease was not increased in patients receiving the prophylactic strategy.…”
Section: Discussionmentioning
confidence: 74%
“…In order to circumvent the occurrence of late HCMV disease after prophylaxis, attempts have been made to prolong prophylaxis to 6 months [25,26]. In our study, late onset HCMV disease was not increased in patients receiving the prophylactic strategy.…”
Section: Discussionmentioning
confidence: 74%
“…Some evidence suggests that prolonging prophylaxis up to 6 months may reduce the incidence of late-onset infections (7,10,11). However, preliminary study of our material showed a high frequency of late-onset primary CMV infections in 48% of patients despite prolonged 6 months prophylaxis with valganciclovir (12) (5,9).…”
Section: Despite Modern Prevention and Treatment Strategies Infectiomentioning
confidence: 67%
“…After 3 months of antiviral prophylaxis, late-onset primary CMV infections are reported to occur in 18-31% of kidney transplant recipients (7)(8)(9). Evidence suggests that prolonging prophylaxis for 6 months reduces the incidence of late-onset infections (7,10,11). In a study by Doyle et (26,27), a novel strategy to predict CMV infections could be to measure CMV-specific T-cell responses (20,(28)(29)(30).…”
Section: Despite Modern Prevention and Treatment Strategies Infectiomentioning
confidence: 99%
“…A metaanalysis of 11 randomized trials (698 patients; median follow-up: 12 months, range: 3-22 months), with six randomized trials (302 patients) after kidney transplantation, demonstrated a beneficial effect of the prophylactic use of CMV immunoglobulin on total survival and prevention of Should not be used 1500 mg once a day, or 500 mg three times a day Should not be used 1000 mg once a day, or 500 mg twice a day [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Should not be used 500 mg once a day <10…”
Section: Antiviral Medications For Universal Prophylaxis and Preemptimentioning
confidence: 99%